2007
DOI: 10.1111/j.1750-3841.2007.00520.x
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation of Calcium‐Fortified Soymilk with Lactobacillus: Effects on Calcium Solubility, Isoflavone Conversion, and Production of Organic Acids

Abstract: The objective of this study was to enhance calcium solubility and bioavailability from calcium-fortified soymilk by fermentation with 7 strains of Lactobacillus, namely, L. acidophilus ATCC 4962, ATCC33200, ATCC 4356, ATCC 4461, L. casei ASCC 290, L. plantarum ASCC 276, and L. fermentum VRI-003. The parameters that were used are viability, pH, calcium solubility, organic acid, and biologically active isoflavone aglycone content. Calcium-fortified soymilk made from soy protein isolate was inoculated with these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 33 publications
2
28
0
3
Order By: Relevance
“…This oxalic acid form insoluble calcium oxalate salts (Jadhav et al, 2015). An increase in calcium solubility and availability was observed in the studies of Tang et al (2007) who fed the birds with Lactobacillus strains which is attributed to its ability to reduce the gut pH due the production of lactic and acetic acids.…”
Section: Organic Acidsmentioning
confidence: 99%
“…This oxalic acid form insoluble calcium oxalate salts (Jadhav et al, 2015). An increase in calcium solubility and availability was observed in the studies of Tang et al (2007) who fed the birds with Lactobacillus strains which is attributed to its ability to reduce the gut pH due the production of lactic and acetic acids.…”
Section: Organic Acidsmentioning
confidence: 99%
“…2 and the ingredients of the culture medium may remain in the final product. Since the culture medium may contain some allergens such as milk and soy, declaration of allergen may be needed for some probiotics, if any allergen is used during production and its complete elimination from the final product cannot be confirmed (Rasic and Kurmann 1983;Tang et al 2007). However, because of the differences in the allergen list between countries, manufacturers of probiotics need to know the list for each country or region where probiotic products will be marketed.…”
Section: Regulatory Controlmentioning
confidence: 99%
“…It has been reported that Lactobacillus gasseri SBT0270 could exert a hypocholesterolemic effect in rats fed a diet high in cholesterol (Usman and Hosono 2000). It has also been reported that probiotics can potentially enhance the calcium bioavailability of calcium-fortified soymilk, due to increased calcium solubility and bioactive isoflavone aglycone enrichment (Tang et al 2007). Probiotics seem to be important in foods containing dietary isoflavones.…”
Section: Introductionmentioning
confidence: 97%